Correlation between Knowledge, Attitude and Performance of the Employees with Quality Asurance System Implementation by the Employers - H Dargahi; M Rezaiian (Tehran University of Medical Sciences, 2007)
Background: Quality assurance is implemented by the framework for the ISO 9001- 2000 " Quality Management System "and ISO 15189: 2003. QA system will be more efficient if every organization's employees are commitment to QA implementation. This survey aimed to correlate between knowledge, attitude and performance of the employees with QA system implementation and its indicators observation in Tehran University of Medical Sciences Hospitals' Clinical Laboratories in 2003-2005. Methods: A Cross- sectional, descriptive analytical survey was accomplished with two types of questionnaires to collect Employees' demographic information and determine knowledge, attitude and performance of the employees about QA system and its indicators observation in TUMS Hospitals Laboratories. Also, a checklist including 685 questions published by WHO and ISO 15189: 2003 requirement series was made to monitor preanalytical, analytical, and postanalytical stage of fourteen TUMS Hospitals' Clinical Laboratories. The data was saved by spss software and analyzed by statistical method. Results: The results showed that knowledge, attitude and performance of the employees for implementation and ob-servation of QA system and its indicators are more increased and positive with increased level of their academic degrees. Conclusion: QA programs and indicators would be programmed if all of the employees participated to implement QA programs in these laboratories.